THE "FITNESS AGE" CONSTRUCT IN CONSUMER WEARABLES: A CRITICAL REVIEW OF PHYSIOLOGICAL VALIDITY AND THE PSYCHOSOCIAL IMPACT ON CARDIOVASCULAR PATIENT IDENTITY - Łukasz Chojnowski; Mariusz Suchcicki; Karol Krupiniewicz; Miłosz Rogiński; Marek Wojciechowicz; Stanisław Rogiński; Katarzyna Mazurek; Anna Dominiczak; Marta Brzęcka; Krzysztof Rogiński (International Journal of Innovative Technologies in Social Science, 2026)
Background. Consumer wearables increasingly translate complex physiological data into simplified constructs intended for everyday users. One of the most influential of these is “Fitness Age” (FA), a proprietary metric primarily derived from estimated VO₂ max, resting heart rate, and activity patterns. Although widely adopted by patients and recreational athletes, its clinical validity and psychosocial consequences remain insufficiently examined, particularly in cardiovascular populations.Objective. This review critically evaluates the physiological foundations of the Fitness Age construct and explores its impact on patient health identity and illness perception, with particular relevance for cardiovascular care.Methods. A systematic review was conducted in accordance with PRISMA 2020 guidelines, covering publications from 2015 to 2026. Physiological validation studies comparing wearable-derived metrics with clinical gold standards (CPET, ECG, Holter monitoring) were analyzed alongside qualitative and quantitative research addressing psychosocial outcomes.Results. High-end Garmin wearables demonstrate strong accuracy for resting heart rate and nocturnal heart rate variability, while estimated VO₂ max shows a consistent error margin of approximately 5–8% in clinical cohorts. Psychosocially, Fitness Age functions as a powerful motivational tool but may also contribute to algorithm-driven anxiety and altered patient identity, particularly in individuals with established cardiovascular disease.Conclusions. Fitness Age should be interpreted as a behavioral and motivational proxy rather than a diagnostic indicator. Clinicians must actively contextualize wearable-derived metrics to harness their preventive potential while minimizing psychological harm.